Green human resources in higher education institutions: a systematic literature review - Zuria Akmal, Saad; Muhammad Ashraf, Fauzi; Laili, Zulkepeli; Moshood, Taofeeq D.; Suhaidah, Hussain (Emerald Publishing Limited, 2024)
Purpose: The purpose of this study is to conduct a comprehensive examination of the concept of green human resources management (GHRM) within the context of higher education institutions (HEIs). The GHRM concept has emerged from the broader environmental management concept in the last decade. Its adoption has diffused in many sectors, particularly manufacturing, but empirical studies in HEIs are lacking. HEIs, as the epitome of knowledge creation and dissemination, should lead the GHRM initiative as an example to the corporate world and the public. Design/methodology/approach:The approach applied is based on the systematic literature review approach to draw inferences, analyze and summarize past studies based on the PRISMA method. Several research streams were identified: (1) academic and non-academic GHRM, (2) theoretical foundation, (3) qualitative and quantitative studies, and (4) green training and development. Findings: This review discovered that GHRM implementation in HEIs leads to better sustainability efforts within academic institutions. It is relevant to stakeholders, policymakers, and HEIs’ top management to strategize in making the academic institution the torchbearer of sustainable practice and a role model for other sectors and communities. Practical implications: This study provides implications towards the application of GHRM in HEIs to elevate academic institutions as the torchbearers for sustainability development. The implicit findings based on the research streams produced can benefit future studies in HEIs to adopt best practices in green activities, particularly GHRM. The implication of GHRM in HEIs would impart individual green, cautious, and sustainability practices holistically and comprehensively, improving behavior towards overall higher education activities involving academics, students, administrative staff, and the overall community ecosystem. Originality/value: This study makes a significant contribution to the existing literature by systematically elucidating the role of GHRM in HEIs, providing insights for academics and policymakers seeking to promote sustainable practices.